2020
DOI: 10.3390/antiox9070639
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antioxidant Effects of Regular Consumption of Cooked Ham Enriched with Dietary Phenolics in Diet-Induced Obese Mice

Abstract: Oxidative damage and chronic inflammation have been proven as one of the major factors associated with obesity, which increases the incidence of non-communicable chronic diseases. In this sense, the development of new functional products aiming at the palliation of oxidative stress and inflammatory disruption can be a determining factor for public health as seen in previous researches. In this study, a blend of potentially bioavailable dietary phenolics was added to low sodium and low-fat cooked ham. A diet-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Therefore, they might be considered one of the first functional foods. Experimental evidence supports the health benefits attributed to spices and herbs, for example, cardio-protective and anti-atherogenic potential, digestive stimulant action, antidiabetic effects, antilithogenic properties, cancer-preventive potential and anti-inflammatory properties [83][84][85].…”
Section: Thyme As Functional Foodmentioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, they might be considered one of the first functional foods. Experimental evidence supports the health benefits attributed to spices and herbs, for example, cardio-protective and anti-atherogenic potential, digestive stimulant action, antidiabetic effects, antilithogenic properties, cancer-preventive potential and anti-inflammatory properties [83][84][85].…”
Section: Thyme As Functional Foodmentioning
confidence: 77%
“…Infusions of thyme have been used for their health benefits for thousands of years as a cold treatment, antispasmodic, a carminative agent, traditional medicine in digestive problems and an expectorant for upper respiratory tract infections. In addition, the potential therapeutic effects of thymol have been used for the treatment of disorders affecting different organ systems, such as the cardiovascular, nervous, and respiratory systems [83][84][85].…”
Section: Thyme As Functional Foodmentioning
confidence: 99%
“…For this, TBARs, Hy, and protein carbonyls are considered biomarkers of cell damage: their increase can be generated by oxidative stress and a boost of oxygen reactive substances (ROS). Additionally, FRAP values allow an overall evaluation of plasma antioxidant capacity ( 53 , 54 ). It is well known that the dietary assumption of high amounts of substances with antioxidant activity results in the transfer of these molecules to different animal tissues, usually followed by a significant increase in their total antioxidant capacity ( 55 ), and that several polyphenolic molecules in plants possess antioxidant activities ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thyme extract might be an effective treatment of chronic respiratory diseases accompanied by the inflammation and hypersecretion of mucus [ 120 ]. Previous studies have reported that thymol demonstrates anti-inflammatory, anti-carcinogenic, and immunomodulatory properties, decreased serum lipids, visceral fat accumulation, and reduced blood pressure in experimental models [ 121 , 122 ]. Thyme essential oils have exhibited antifungal and antibacterial bioactivity against both food spoilage microflora and pathogenic microflora in vitro, including B. subtilis , S. aureus , S. enteritidis , and P. aeruginosa [ 123 ].…”
Section: Bioactive Compounds and Antibacterial And Antioxidant Activi...mentioning
confidence: 99%